DESEMPENHO DE FUNÇÕES DE DENSIDADE PROBABILÍSTICAS PARA DESCREVER A DISTRIBUIÇÃO DIAMÉTRICA DE Pinus taeda, NA REGIÃO DE CAÇADOR, SC - Téo, Saulo Jorge; Bianchi, Júlio César; Peloso, Adriano; Nava, Paulo Roberto; Marcon, Alan; Ehlers, Tiago; Costa, Reinaldo Hoinacki da (Floresta, 2012)
Resumo O objetivo deste trabalho foi analisar as funções de densidade probabilísticas (FDP) Normal, Ln-Normal, Sb de Johnson, Weibull 3P, Gamma, Beta e Weber, para descrever as mudanças na estrutura diamétrica de povoamentos de Pinus taeda L., na região de Caçador (SC), em diferentes idades e classes de sítio. O processamento dos dados foi realizado por meio da ferramenta Solver, do software MS Excel 2010, a qual utiliza o algoritmo linear de gradiente reduzido generalizado (GRG) na interação dos parâmetros. Verificou-se que a FDP Sb de Johnson e Weibull 3 P apresentaram os melhores desempenhos. Para a avaliação da aderência das FDP, é recomendada a utilização das estatísticas R2, R2aj, syx e syx%, além do teste de Kolmogorov-Smirnov, em todos os casos, especialmente quando houver número de observações superior a 5.000. Geralmente, houve um aumento da amplitude dos valores dos diâmetros e um achatamento da distribuição diamétrica com o avanço da idade e com a melhora da produtividade do sítio. Com o progresso da idade, há um aumento dos valores do diâmetro máximo e do diâmetro modal das distribuições, para as classes de sítio de maior produtividade, porém o mesmo não ocorre para o sítio menos produtivo. Abstract Performance of probability density functions in order to describe diameter distribution of Pinus taeda, in the region of Caçador, SC. This research aims to analyze probability of density functions (pdf) Normal, Ln-Normal, Johnson Sb, 3 P Weibull, Gamma, Beta and Weber in order to describe diameter changes in Pinus taeda L. plantations structure, in the region of Caçador - SC, Brazil, at different age and site classes. The data processing was carried out by Solver tool of the software MSExcel2010, using the linear algorithm of generalized reduced gradient (GRG) for interaction of parameters. As result, Johnson Sb and 3PWeibull presented the best performances. For the pdf adherence evaluation, it was recommended the employment of R2, R2aj, syx e syx% statistics, besides the Kolmogorov-Smirnov test, in any situation, specially, when there is more than 5,000 observations. Generally, there was an increasing in the range of diameter values and a flatness of diameter distribution at advancing age and improvement of the site productivity. At age advancing, there was an increasing of maximum diameter and modal diameter values of distributions, for the higher productivity site classes, on the other hand, the same did not occur for the low productivity site class. Keywords: Horizontal structure; Kolmogorov-Smirnov test; probability density function; forestry site.